Synthesis of Polynitrostilbenes using Activated Hydrotalcites as Heterogeneous Base Catalysts. (October 2014) - Xu, Junhui; Wei, Jianping; Ma, Qingguo; Peng, Xinhua
An efficient and straight for ward synthesis of polynitrostilbenes with the ( E )-configuration by the condensation of polynitroarenes with aromatic aldehydes, catalysed by activated hydrotalcites as heterogeneous catalysts is described.